The Development of Instructional Packages on the Development of Thailand in the Rattanakosin Period with Inquiry-Based Learning (5E) to Promote Academic Achievement in History for Prathomsuksa 6 Students - Kaewcharee, Kanitta; Busayanon, Kanrawee (Suan Dusit Graduate School Academic Journal, 2025)
The objectives of this research were to: 1) compare the academic achievement of Prathomsuksa 6 students before and after using the instructional packages on the development of Thailand in the Rattanakosin period, along with inquiry-based learning (5E); and 2) study the satisfaction of Prathomsuksa 6 students using the instructional packages on the development of Thailand in the Rattanakosin period, along with inquiry-based learning (5E). The participants in the research were 27 Prathomsuksa 6 students at Pracha-Uppatham School during the second semester of the 2023 academic year. The research instruments included:1) the instructional packages on the development of Thailand in the Rattanakosin period, 2) lesson plans using inquiry-based learning (5E), 3) an academic achievement test, and 4) a satisfaction assessment form. Statistics used in data analysis included mean, standard deviation, and dependent sample t-test. The research results were as follows: 1) Academic achievement of Prathomsuksa 6 students after studying with the instructional packages on the development of Thailand in the Rattanakosin period combined with inquiry-based learning (5E) was higher than before studying at the statistical significance level of .05. 2) The Prathomsuksa 6 students’ overall satisfaction towards learning using the instructional packages on the development of Thailand in the Rattanakosin period combined with inquiry-based learning (5E) was found at the high level.